Ventriculo-arterial (un)coupling in septic shock: Impact of current and upcoming hemodynamic drugs - Demailly, Zoé; Besnier, Emmanuel; Tamion, Fabienne; Lesur, Olivier (Frontiers in Cardiovascular Medicine, 2023)
Sepsis is the archetype of distributive shock and combines at different levels alterations in preload, afterload, and often cardiac contractility. The evolution of therapeutics over the last few years goes with the evolving invasive and noninvasive tools to measure these components in real time, but none of them is without flaws, and the mortality of septic shock remains too high. The concept of ventriculo-arterial coupling (VAC) allows for the integration of these three fundamental macroscopic hemodynamic components. In this mini-review the knowledge, tools, and limitations of VAC measurement are discussed, and then the evidence for ventriculo-arterial uncoupling in septic shock is displayed. Finally, the impact of recommended hemodynamic drugs and molecules on VAC is detailed.